Effect of perioperative intravenous lidocaine for patients undergoing spine surgery: A meta-analysis and systematic review. Issue 48 (25th November 2020) - Bi, Yaodan; Ye, Yu; Ma, Jun; Tian, Zerong; Zhang, Xiuqian; Liu, Bin
Abstract: Background: Perioperative intravenous lidocaine has been reported to have analgesic and opioid-sparing effects in many kinds of surgery. Several studies have evaluated its use in the settings of spine surgery. The aim of the study is to examine the effect of intravenous lidocaine in patients undergoing spine surgery. Methods: We performed a quantitative systematic review. Databases of PubMed, Medline, Embase database and Cochrane library were investigated for eligible literatures from their establishments to June, 2019. Articles of randomized controlled trials that compared intravenous lidocaine to a control group in patients undergoing spine surgery were included. The primary outcome was postoperative pain intensity. Secondary outcomes included postoperative opioid consumption and the length of hospital stay. Result: Four randomized controlled trials with 275 patients were included in the study. postoperative pain compared with control was reduced at 6 hours after surgery (WMD −0.50, 95%CI, −0.76 to −0.25, P  < .001), at 24 hours after surgery (WMD −0.50, 95%CI, −0.70 to −0.29, P  < .001) and at 48 hours after surgery (WMD −0.57, 95%CI, −0.96 to −0.17, P  = .005). The effect of intravenous lidocaine on postoperative opioid consumption compared with control revealed a significant effect (WMD −15.36, 95%CI, −21.40 to −9.33 mg intravenous morphine equivalents, P  < .001). Conclusion: This quantitative analysis of randomized controlled trials demonstrated that the perioperative intravenous lidocaine was effective for reducing postoperative opioid consumption and pain in patients undergoing spine surgery. The intravenous lidocaine should be considered as an effective adjunct to improve analgesic outcomes in patients undergoing spine surgery. However, the quantity of the studies was very low, more research is needed.